Determination of the quality of water for human consumption through physicochemical and microbiological parameters of the city of Pampas - Tayacaja, 2023 - Esmila Yeime, Chavarría Marquez (2024)
The present study was carried out in the city of Pampas, located at 3276 meters above sea level. southwest of the province of Tayacaja, department of Huancavelica during the period April to December 2022, with the objective of determining the quality of water for human consumption through physicochemical and microbiological parameters of the city of Pampas-Tayacaja. The study is of an applied type, descriptive and transectional level, it involved an evaluation as it is presented in reality, that is, without manipulation of variables. At the six sampling stations, physical, chemical and microbiological parameters were evaluated taking as reference the water quality regulation for human consumption D.S. N° 031-2010-SA of the Ministry of Health and the National Environmental Quality Standards for Water DS.N° 004-2017-MINAN, category 1. The results demonstrate that the physicochemical and microbiological parameters of the water of the city of Pampas do not exceed to the values established in the ECA – category 1 water. Therefore, it is concluded that the water from Pampas – Tayacaja is suitable for human consumption, however, periodic controls must be carried out to ensure the quality of the water, even more so if it has oscillations in water formation and hourly service only.